Cannibalizing the Informal Economy: Frugal Innovation and Economic Inclusion in Africa. Issue 1 (January 2018) - Meagher, Kate
Abstract This paper argues that, far from collaborating with informal economic systems and actors, frugal innovation tends to treat informal economies as a pool of workers and organizational resources to be tapped for the benefit of corporate actors. I will examine how frugal innovation models selectively transform informal economic and institutional systems around formal economic interests, reconfiguring informal opportunities and the distribution of gains in ways that promote adverse incorporation of informal actors rather than mutual benefit. I will examine four mechanisms of adverse incorporation operating within frugal innovation models: copying, free-riding, bypassing nodes of accumulation and shifting risk. Drawing on case studies of M-Pesa and micro-insurance, I will illustrate the often selective and disempowering effects of frugal innovation, which operate to reconfigure informal economic systems in ways that divert profits and control away from informal operators. Cet article fait valoir que, loin de collaborer avec les systèmes et les acteurs économiques informels, l'innovation frugale tend à traiter les économies informelles comme une source de main d'oeuvre et de ressources organisationnelles à exploiter au profit des entreprises. Je vais étudier comment les modèles d'innovation frugale transforment de façon sélective les systèmes économiques et institutionnels informels en faveur des intérêts économiques formels; ces modèles transforment des opportunités informelles et la répartition des gains de manière à favoriser l'intégration négative des acteurs informels (à leurs dépens) plutôt que de promouvoir des avantages mutuels. Je vais examiner quatre mécanismes d'intégration négative qui sont à l'oeuvre dans les modèles d'innovation frugale: la copie, le parasitisme, le contournement des noeuds d'accumulation et le déplacement du risque. En s'appuyant sur des études de cas de M-Pesa et de la micro-assurance, je vais illustrer les effets souvent sélectifs et paralysants de l'innovation frugale, qui sont à l'oeuvre pour reconfigurer les systèmes économiques informels de manière à éloigner les profits et le contrôle des opérateurs informels.